Multiple TaqMan qPCR and droplet digital PCR (ddPCR) diagnostics for pesticide resistance monitoring and management, in the major agricultural pest Tetranychus urticae. Issue 1 (22nd September 2021) - Mavridis, Konstantinos; Papapostolou, Kyriaki Maria; Riga, Maria; Ilias, Aris; Michaelidou, Kleita; Bass, Chris; Van Leeuwen, Thomas; Tsagkarakou, Anastasia; Vontas, John
Abstract: BACKGROUND: Decisions on which pesticide to use in agriculture are expected to become more difficult, as the number of available chemicals is decreasing. For Tetranychus urticae (T. urticae), a major pest for which a number of candidate markers for pesticide resistance are in place, molecular diagnostics could support decision‐making for the rational use of acaricides. RESULTS: A suite of 12 TaqMan qPCR assays [G314D ( GluCl1 ), G326E, I321T ( GluCl3 ), G119S, F331W ( Ace‐1 ), H92R ( PSST ), L1024V, F1538I ( VGSC ), I1017F ( CHS1 ), G126S, S141F, P262T ( cytb )], were validated against Sanger‐sequencing, and subsequently adapted for use with the ddPCR technology. The concordance correlation coefficient between the actual and ddPCR measured mutant allelic frequencies was 0.995 (95% CI = 0.991–0.998), and no systematic, proportional, or random differences were detected. The achieved Limit of Detection (LoD) was 0.1% (detection of one mutant in a background of 999 wild type mites). The ddPCR assay panel was then assessed in terms of agreement with phenotypic resistance, through a pilot application in field populations from Crete, with strong correlation and thus predictive and diagnostic value of the molecular assays in some cases (e.g., etoxazole and abamectin resistance). Molecular diagnostics were able to capture incipient resistance that was otherwise missed by phenotypic bioassays. The molecular and phenotypic resistance screening of T. urticae field populations from Crete, revealed both multi‐resistant and susceptible populations. CONCLUSION: The highly sensitive T. urticae molecular diagnostic platforms developed in this study could prove a valuable tool for pesticide resistance management. © 2021 Society of Chemical Industry. Abstract : Molecular diagnostics (simple TaqMan qPCR or high‐tech ddPCR) could aid in the management of Tetranychus urticae, a major pest for which well‐characterized markers of pesticide resistance are in place.